1977
DOI: 10.1126/science.918668
|View full text |Cite
|
Sign up to set email alerts
|

Odor-Aversion Learning in Neonatal Rats

Abstract: Two-day-old rats were exposed to a novel odor and injected with an illness-inducing drug, lithium chloride. When tested at 8 days of age, these pups avoided pine shavings scented with the odor, whereas control pups did not. These results imply that rat pups are capable of associative learning at a much earlier age than was thought possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(93 citation statements)
references
References 6 publications
1
92
0
Order By: Relevance
“…The neural pathways serving the RM CR did not elicit parallel changes in HR as would be expected if the two systems were coupled together centrally (Obrist, 1981). The capacity of the newborn group to form a RM CR within the first 3 days of birth is consistent with experiments (L. T. Martin & Alberts, 1982;Rudy & Cheatle, 1977) demonstrating successful conditioning in very young rats (2-3 days of age). In contrast to the present findings, one of these studies (L. T. Martin & Alberts, 1982) showed conditioning of HR.…”
Section: Discussionsupporting
confidence: 73%
“…The neural pathways serving the RM CR did not elicit parallel changes in HR as would be expected if the two systems were coupled together centrally (Obrist, 1981). The capacity of the newborn group to form a RM CR within the first 3 days of birth is consistent with experiments (L. T. Martin & Alberts, 1982;Rudy & Cheatle, 1977) demonstrating successful conditioning in very young rats (2-3 days of age). In contrast to the present findings, one of these studies (L. T. Martin & Alberts, 1982) showed conditioning of HR.…”
Section: Discussionsupporting
confidence: 73%
“…Until the emergence of amygdala function at PN10, neonatal pups do not express both learned and unlearned fear (Sullivan et al, 2000;Takahashi, Turner, & Kalin, 1991;Wiedenmayer & Barr, 2001). It should be noted that very high-intensity shock (1.0-1.5 mA) does produce an odor aversion in neonatal pups via odorillness conditioning (Camp & Rudy, 1988;Haroutunian & Campbell, 1979;Kucharski & Spear, 1984;Rudy & Cheatle, 1977;Sullivan & Wilson, 1995), although this conditioning has been shown to occur without an amygdala (Bermudez-Rattoni & Mc-Gaugh, 1991;Schafe, Thiele, & Bernstein, 1998). Interestingly, while odor illness is easily learned by pups away from the mother, this learning is attenuated if conditioning is done while pups are suckling, indicating another constraint on pups' learning (Thiels & Alberts, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One might therefore expect to find age-related changes in the ability of the rat to form certain types of association. Indeed, it has been shown that, whereas interoceptive reinforcers [such as food or lithium chloride (LiCl)] can promote associations in Ito 2-day-old rats (Johanson & Hall, 1979;Rudy & Cheatle, 1977), exteroceptive reinforcers (such as peripherally applied electric shock) are effective in establishing associative bonds only in rats older than 10 days of age (Haroutunian & Campbell, 1979). It may be, therefore, that the ability of neonatal rats to form associations that incorporate information about a conditioned reinforcer may occur later in development than the age at which Cheatle and Rudy (1978) tested their rats.…”
Section: Second-order Flavor Aversion 317mentioning
confidence: 99%